Towards a patient-centred approach in therapeutic patient education. A qualitative study exploring health care professionals' practices and related representations. (June 2023) - Roussel, Sandrine; Frenay, Mariane
Objectives: This study aimed to explore the practice-representation links among Health Care Professionals (HCP)s practising Therapeutic Patient Education (TPE). Understanding these links might actually help to address the challenges of TPE implementation, particularly the patient-centred dimension. Methods: A qualitative study using individual interviews was conducted with HCPs practising in French-speaking Belgium or in France. Data analysis was carried out in two steps: to draw up a typology of educational practices (including variations) and, in line with the Social Representation Theory, to identify possible related social representations. Results: The typology, based on HCP-Patient power distribution, was built from 26 interviews. Four types and nine subtypes were identified. Besides the power distribution, practice (sub)types were also specific regarding communication modes, consideration for patients' representations, motivational approach, personalization, complexity of methods and learning contents, and practice reflexivity. Practices were seldom constant. Three variations were highlighted: within a subtype, between different subtypes, and between education and technical care. Both practice subtypes and variations were related to specific decisive representations. Discussion: Representations related to practices and those related to practices variations offer new perspectives for TPE implementation. There is no panacea for achieving more patient-centred approaches; tailored strategies based on practice subtypes are needed.